Equity Mutual Funds Performance Assessment in Indonesia and Its Determinants - Dayan Cahya Pradipta (iBuss Management, 2018)
Mutual funds, which used to be an overlooked investment vehicle in Indonesia, has been growing rapidly in terms of its market participants and capitalization. Strong macro-economic improvements have positively stimulated the investing ecosystem, triggering new mutual funds, especially equity-based mutual funds, to emerge and attracts new investors. With more options available in the market, investors needs to be able to accurately analyze the performance of equity mutual funds. In this research, the researcher analyzes the performance of equity mutual funds, its related skills on Stock Selection and Market Timing, and its determinants namely Fund Size, Fund Age, Load Fee, Expense Ratio, Portfolio Turnover and Affiliation to Securities Companies.Data of 122 equity mutual funds in Indonesia during 2012-2017 were collected from Bloomberg Terminal as well as the annual report and prospectus of each fund. To analyze the data, the researcher used simple and multiple linear regressions. The regressions results show that there are 17 equity mutual funds that outperformed the market, with the outperformance can be attributed to Stock Selection Ability. The findings also suggest that all the mentioned determinants do not significantly influence equity mutual fund’s performance in Indonesia. Keyword: Mutual Fund Performance, Stock Selection Ability, Market Timing Ability, Performance Determinant